Autophagy gene ATG7 regulates ultraviolet radiation-induced inflammation and skin tumorigenesis. Issue 12 (2nd December 2017) - Qiang, Lei; Sample, Ashley; Shea, Christopher R.; Soltani, Keyoumars; Macleod, Kay F.; He, Yu-Ying
ABSTRACT: Macroautophagy (hereafter autophagy) is a cellular "self-eating" process that is implicated in many human cancers, where it can act to either promote or suppress tumorigenesis. However, the role of autophagy in regulation of inflammation during tumorigenesis remains unclear. Here we show that autophagy is induced in the epidermis by ultraviolet (UV) irradiation and autophagy gene Atg7 promoted UV-induced inflammation and skin tumorigenesis. Atg7 regulated UV-induced cytokine expression and secretion, and promoted Ptgs2/Cox-2 expression through both a CREB1/CREB-dependent cell autonomous mechanism and an IL1B/IL1β-dependent non-cell autonomous mechanism. Adding PGE2 increased UV-induced skin inflammation and tumorigenesis, reversing the epidermal phenotype in mice with Atg7 deletion in keratinocytes. Similar to ATG7 knockdown in human keratinocytes, ATG5 knockdown inhibited UVB-induced expression of PTGS2 and cytokines. Furthermore, ATG7 loss increased the activation of the AMPK pathway and the phosphorylation of CRTC1, and led to endoplasmic reticulum (ER) accumulation and reduction of ER stress. Inducing ER stress and inhibiting calcium influx into the ER by thapsigargin reverses the inflammation and tumorigenesis phenotype in mice with epidermal Atg7 deletion. Taken together, these findings demonstrate that deleting autophagy gene Atg7 leads to a suppression of carcinogen-induced protumorigenic inflammatory microenvironment and tumorigenesis of the epithelium.